2015
DOI: 10.1155/2015/539408
|View full text |Cite
|
Sign up to set email alerts
|

The Impact ofLEPG-2548A andLEPRGln223Arg Polymorphisms on Adiposity, Leptin, and Leptin-Receptor Serum Levels in a Mexican Mestizo Population

Abstract: The polymorphisms in leptin (LEP G-2548A) and leptin-receptor (LEPR Gln223Arg) seem to influence obesity and lipid metabolism among others. The aim of this study was to investigate the effect of these polymorphisms on adiposity, leptin (sLeptin), and leptin-receptor (sLeptin-receptor) serum concentrations as well as inflammation markers. We included 382 adults originally from Western Mexico. They were genotyped by PCR-RFLP. Obese individuals showed higher sLeptin (58.2 ± 31.35 ng/mL) but lower sLeptin-receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
0
17
1
1
Order By: Relevance
“…This polymorphism had no effect on breast cancer risk in our study. There are inconsistent reports on its effect on leptin levels with the AA genotype in Indians [36] and the G allele in Mexicans having higher leptin levels [37]. Despite a reduced leptin signaling implicated for the LEPR Q223R/Gln223Arg A>G (rs1137101) [38] polymorphism, it has shown inconsistent results on breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…This polymorphism had no effect on breast cancer risk in our study. There are inconsistent reports on its effect on leptin levels with the AA genotype in Indians [36] and the G allele in Mexicans having higher leptin levels [37]. Despite a reduced leptin signaling implicated for the LEPR Q223R/Gln223Arg A>G (rs1137101) [38] polymorphism, it has shown inconsistent results on breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Boumaiza et al (2012) also showed that G2548A has significant association with obesity 33 . Zayani et al 2018 were also found a significant association between Q223R and G2548A SNPs and obesity 39. S u r ya p ro m et a l 2 0 1 4 l i kew i s e demonstrated that there was a relationship between LEPR Gln223Arg polymorphism and Leptin Level and metabolic disorder 34,35 . Farooq et al similarly demonstrated that leptin assumes a basic role in particularly, ovulation and spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…There are a couple of studies dealing with the connection between LEP G2548A and LEPR Gln223Arg polymorphisms, obesity and daily energy intake. Significantly more important, these linked are showing up in a racial dependent design [32][33][34] . Likewise, the relationship of G2548A and Gln223Arg gene polymorphism with unexplained infertility among Indian has not been examined till date.…”
Section: Association Of Lep G2548a and Lepr Gln223arg Gene Polymorphimentioning
confidence: 99%
“…In particular, the original study reporting the European ancestral association between rs1137101 and OSA was conducted in a population from Poland with PSG-confirmed cases and controls matched for age, gender and BMI 66 . Given the strong relationship between OSA and obesity, it is interesting to note that these LEPR SNPs are reported in more than one study to be unassociated with risk for obesity 6769 , suggesting variation in the LEPR gene may have effects on expression of OSA that are independent of obesity. It is unclear what are the functional consequences of these two missense mutations in LEPR ; however, both are reported in ClinVar as benign (https://www.ncbi.nlm.nih.gov/clinvar/).…”
Section: Discussionmentioning
confidence: 99%